2016
DOI: 10.1002/jsfa.7793
|View full text |Cite
|
Sign up to set email alerts
|

Chalky part differs in chemical composition from translucent part of japonica rice grains as revealed by a notched‐belly mutant with white‐belly

Abstract: BACKGROUNDChalkiness has a deleterious influence on rice appearance and milling quality. We identified a notched‐belly mutant with a high percentage of white‐belly, and thereby developed a novel comparison system that can minimize the influence of genetic background and growing conditions. Using this mutant, we examined the differences in chemical composition between chalky and translucent endosperm, with the aim of exploring relations between occurrence of chalkiness and accumulation of starch, protein and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 22 publications
11
47
0
Order By: Relevance
“…The selected wavelengths, although they varied across the classification definitions, indicated that the discrimination was partially based on starch, protein, and water adsorption bands. These results are similar to the findings that starch composition and water absorption index differ between chalky and vitreous kernels (Kim, Lee, Kim, & Kim, 2000;Lin et al, 2016;Lisle et al, 2000;Patindol & Wang, 2003). Similarly, the model wavelengths of 1,630 nm for MaxLevel, approximately 1,269 and 1,280 nm for modified GIPSA, and approximately 1,202, 1,280, and 1,631 nm for 10% cutoff corresponded to wavelength absorption bands for protein (Pandiselvam, Thirupathi, Mohan, & Uma, 2015;Shenk et al, 1992;Williams & Norris, 2001).…”
Section: Calibration Model For the Sknir Instrumentsupporting
confidence: 91%
See 4 more Smart Citations
“…The selected wavelengths, although they varied across the classification definitions, indicated that the discrimination was partially based on starch, protein, and water adsorption bands. These results are similar to the findings that starch composition and water absorption index differ between chalky and vitreous kernels (Kim, Lee, Kim, & Kim, 2000;Lin et al, 2016;Lisle et al, 2000;Patindol & Wang, 2003). Similarly, the model wavelengths of 1,630 nm for MaxLevel, approximately 1,269 and 1,280 nm for modified GIPSA, and approximately 1,202, 1,280, and 1,631 nm for 10% cutoff corresponded to wavelength absorption bands for protein (Pandiselvam, Thirupathi, Mohan, & Uma, 2015;Shenk et al, 1992;Williams & Norris, 2001).…”
Section: Calibration Model For the Sknir Instrumentsupporting
confidence: 91%
“…The growing environment significantly influences the formation of rice chalk (Qiao et al, 2011;Tashiro & Wardlaw, 1991). The relatively slow progress in breeding for low chalkiness reflects the complexity of the underlying mechanisms for how rice chalk occurs and how rice interacts with the growing environment (Lin et al, 2016;Liu et al, 2010). Fitzgerald and Resurreccion (2009) also showed that rice chalk increased with high temperature.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations